2018
DOI: 10.1016/j.ultramic.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

An improved FIB sample preparation technique for site-specific plan-view specimens: A new cutting geometry

Abstract: Focused ion beam (FIB) sample preparation technique in plan-view geometry allows direct correlations of the atomic structure study via transmission electron microscopy with micrometer-scale property measurements. However, one main technical difficulty is that a large amount of material must be removed underneath the specimen. Furthermore, directly monitoring the milling process is difficult unless very large material volumes surrounding the TEM specimen site are removed. In this paper, a new cutting geometry i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 18 publications
0
40
0
1
Order By: Relevance
“…Therefore, ion beam milling TEM sample preparation can be considered as a rough method for INCONEL alloy surface microstructure study. Focused ion beam technique have been developed to overcome extensive surface artifact develop by traditional bulk ion beam milling technique [18]. However, focused ion beam milling has its own limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ion beam milling TEM sample preparation can be considered as a rough method for INCONEL alloy surface microstructure study. Focused ion beam technique have been developed to overcome extensive surface artifact develop by traditional bulk ion beam milling technique [18]. However, focused ion beam milling has its own limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work showed that the removal of material behind the region of interest could improve the quality of the EDS image. [14][15][16][17] Figure 1 shows how the lines within the interaction volume delineate the regions where the effect indicated predominates. For example, only X-rays emerge from the sample from the deeper parts of the sample and the depth of this interaction volume can be calculated and simulated with a Monte Carlo simulation.…”
Section: Introductionmentioning
confidence: 99%
“…For SPM characterization the lamella is then lifted out using an EasyLift EX lift-out needle. Using a combination of motorized needle rotation and a pre-tilt stub, it is possible to put down the lamella in a single step, i.e., without any transfer steps as commonly used in planview lamella preparation (which requires a similar 90 • rotation between plan-view and cross-section geometry 36 ). This process is illustrated in Figure 2: The needle is attached [ Figure 2 700 nm and polished with the 30 kV beam at a glancing angle of 3 • -5…”
mentioning
confidence: 99%